Analisis Standar Pembiayaan Pendidikan - Akhmad Aflaha; Deden Purbaya; Dedeng Juheri; Ujang Cepi Barlian (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2021)
Funding is an important part of the management of educational institutions in achieving educational goals. Education financing can be formulated into four steps, namely; education financing concept, education financing model, education financing formulation, and education financing measurement. The objective of standardizing financing through the concept of education financing is to determine the budgeting mechanism; The financing model is an effort to divide financing through two sides, namely the allocation side and the income side; The formulation of education financing is an effort to divide the financing model through the source model of the proof or acceptance letter model, the student weight planning model, the model based on experience, the model based on wisdom and Measurement of education financing is carried out in order to assess management performance with fairness of financing. The results of the analysis of education financing standards can be concluded: First, the concept of education financing, which is a determining element in the budgeting mechanism. The determination of costs will affect the level of efficiency and effectiveness of activities in an organization to achieve its goals. Second, the education financing model. In principle, the education financing model has two sides, namely the allocation side and the income side. Third, the formulation of education financing is different from one another, namely; a) source model; b) proof letter model; c) student weight planning model; d) a model based on experience; e) proposed model and; e) wisdom model. Fourth, measuring education financing through reasonableness and policies. Keywords: Analysis, Financing Standards, Education.